80 COMMON POLYMORPHISMS IN MISMATCH REPAIR GENES AND OVARIAN CANCER SURVIVAL. Issue 1 (1st January 2007) - Mann, A. P.; Thompson, D.; Pharoah, P.; Song, H.
Abstract : Ovarian cancer is a complex disease, the etiology and progression of which are thought to be controlled by both genetic and environmental factors. Approximately 10% of epithelial ovarian cancers are hereditary. Highly penetrant, rare mutations in the BRCA1 and BRCA2 DNA repair genes have been identified and account for less than 30% of the excess familial risk of ovarian cancer. Some research has examined the effect of genetic variation in DNA repair genes on breast cancer survival. However, currently, there are no published studies on common inherited variants of the mismatch repair pathway and ovarian cancer survival. The purpose of this study was to examine whether certain germline single-nucleotide polymorphisms (SNPs) in mismatch repair genes were associated with better survival in ovarian cancer patients from East Anglia, UK, Northern California, and Denmark. Cases came from three separate prospective studies, the total population of which consisted of 1, 499 ovarian cancer patients. Each case was genotyped for 48 SNPs in 7 DNA mismatch repair genes. Each SNP was tested for association with ovarian cancer survival using both trend and heterogeneity tests from a Cox regression model adjusted for stage, grade, histology, and age at diagnosis. Significant evidence of association between genotypes and ovarian cancer survival ( p < .05) was seen in one SNP, PMS1 (rs3762545). Borderline evidence of association was shown for SNPs in MSH3 (rs26282), MSH6 (rs2020911), PMS1 (rs256571), and PMS2 (rs2286680 and rs1805324). The results suggest that most of the tagging SNPs in the mismatch repair genes identified for this study are not likely to be associated with ovarian cancer survival. However, significantly improved survival in PMS1 (rs3762545) carriers requires further investigation. With the exception of PMS1 (rs3762545), the number of weak associations observed was not significantly different from what would be expected by chance alone. Investigation of common genetic variants and their effect on ovarian cancer survival should continue as there may be an underlying genetic difference, which affects the clinical course.